A structured Solar System satellite relay constellation network topology design for Earth‐Mars deep space communications. (5th November 2018) - Wan, Peng; Zhan, Yafeng
Summary: The deep space exploration missions require high quality of communication performance between the Earth stations and various deep space explorers, such as Mars orbiters and rovers. Due to the difficulties on improving the point‐to‐point physical wireless link capacity, it is necessary to study the relay network communications under the structured idea. In this paper, the structured Solar System satellite relay constellation network is proposed for Earth‐Mars deep space communications, including the mission background, mathematic model, topology design, and performance analysis. The satellite relay constellation could be modelled as a 2‐dimensional structure with multiple concentric circle loops and multiple relate satellites on each loop. With the different optimal objectives as shortest path, minimum hops and minimum nodes required under the constraint threshold distance for each hop, both the Monte Carlo method and modified Shortest Path First algorithms are studied to work out the optimal network topology designs. Simulation results show that, our network topology design could satisfy the requirements on continuous dual‐directional end‐to‐end communications between the Earth and Mars over the whole mission life period and guarantee the performance of end‐to‐end multihop links above the lowest boundary. Abstract : In this paper, the structured Solar System satellite relay constellation network is proposed for Earth‐Mars deep space communications, which could be modelled as a two‐dimensional structure with multiple concentric circle loops and multiple relate satellite on each loop. Simulation results show that our network topology design could satisfy the requirements on continuous dual‐directional end‐to‐end communications between the Earth and Mars over the whole mission life period and guarantee the performance of end‐to‐end multihop links above the lowest boundary.